2020
DOI: 10.1001/jamasurg.2020.1463
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Immunization for Splenectomy and the Surgeon’s Responsibility

Abstract: plenectomy is a common operation, accounting for at least 25 000 procedures per year in the US. Indications include hematological diseases, traumatic injuries, and benign and malignant gastrointestinal, urological, and gynecologic conditions. The most dreadful sequel of splenectomy is overwhelming postsplenectomy infection (OPSI), a syndrome consisting of a nonspecific prodrome rapidly evolving toward pneumonia, meningitis, or fulminating sepsis. Although several strategies have been embraced, namely antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 80 publications
0
11
0
Order By: Relevance
“…Splenectomy is a routine treatment for splenic rupture and hypersplenism. It increases the risk of various immune‐related diseases, such as infections, tumours and type 2 diabetes (Camprubí et al, 2019 ; Casciani et al, 2020 ). Our study indicates that removal of spleen accelerates the development of AD in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Splenectomy is a routine treatment for splenic rupture and hypersplenism. It increases the risk of various immune‐related diseases, such as infections, tumours and type 2 diabetes (Camprubí et al, 2019 ; Casciani et al, 2020 ). Our study indicates that removal of spleen accelerates the development of AD in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that since the spleen is the largest secondary lymphoid organ in the body, both adaptive and innate immune responses are impaired after a splenectomy. However, whether the splenectomy was associated with his irAEs remains to be further explored [11]. The patient's follow-up NGS examination results were as follows: PD-L1 expression, 5-50% (SP142 antibody) and TMB, 14.77 Muts/Mb, which may explain his better clinical efficacy.…”
Section: Discussionmentioning
confidence: 97%
“…Splenectomy patients have overwhelming post splenectomy infection (OPSI) lifelong risk. A condition associated with high mortality rates (Casciani et al 2020). Encapsulated organisms are frequently associated with sepsis in splenectomies patients.…”
Section: Discussionmentioning
confidence: 99%